From diffusion to contestation: understanding norms in politics - Onursal-Besgul, Ozge; Kaya, Ayhan (Routledge Journals, Taylor & Francis Ltd, 2026)
This Special Issue examines the dynamics of norm diffusion, contestation and localization in Southeast Europe and the Black Sea region, focusing particularly on T & uuml;rkiye. Drawing on research into international organizations, norm diffusion and Europeanization, this issue explores how norms are constructed, disseminated, adapted and challenged in global, regional and domestic contexts. The twelve contributions are organized around four interrelated themes: (1) the reinterpretation of liberal norms and the shifting international order; (2) domestic adaptation, localization, and de-Europeanization; (3) civil society and the politics of norm preservation; and (4) regional and sectoral arenas of norm production, including migration, climate, and gender policies. Together, the articles emphasize the nonlinear, multilevel, and contested nature of normative change. They demonstrate how regional actors, international institutions, and civil society influence, resist, and transform normative orders amid geopolitical shifts and overlapping crises.
Keywords: Norm Diffusion; Contestation; Localization; Europeanization; De-Europeanization; T & Uuml;Rkiye